ROLE OF LIBRARIES IN PROMOTING READING INTEREST (International Journal of Food and Nutritional Sciences, 2022)
Reading is an interesting and important activity in the society, the word reading habit is combination of two words namely ‘reading and habit’. ‘Reading is an action of a person who reads’ and ‘habit is product of this action’ or the learning’. Many users considered reading is a good habit but reading is the basic for the human skills. Reading offers a constructive approach to improve one’s vocabulary and language skills. The thirst of reading and wider dissemination of books is an indicator of progress in the world. Reading is primarily an intellectual activity and reading habit is a sort of attribute of human being, after analysis the views of various scholars in context of reading habit, it is clear that reading is important for people to acquiring new information and knowledge. Thus reading is regarded as a process, a mode of thinking, a kind of real life experience and involves many complex skills.